Pendampingan Manajemen Komunikasi Orang Tua Dalam Penanaman Nilai-Nilai Akhlak Islam Kepada Anak Remaja (Gen-Z) di Era Digital - Nur Azizah; Rina Dwi Wulandari; Sayid Habiburahman; Achmad Tasmi (LP3M IAIFA Kediri, 2025)
The acceleration of digital transformation has led to a communication gap between parents and teenagers (Generation Z), particularly in the community of Tanjung Dayang Selatan Village, Ogan Ilir District. Parents' lack of understanding of Islamic-based parenting in the digital age poses a challenge in nurturing children's moral character. This community service initiative aims to enhance parents'—particularly local mothers'—capacity to manage effective and Islamic-values-based communication with their teenage children. The activities are based on the theory of Islamic family communication and the approach of da'wah bil hikmah. The methods employed include participatory seminars, case study discussions, and interactive question-and-answer sessions over two days. The material is structured around three focuses: the concept of Islamic communication, critical and responsible guidance on digital media use, and the development of empathetic dialogue between parents and children. Pre-post evaluation results show significant improvements in participants' knowledge (+38%), attitudes (+31%), and skills (+27%). Additionally, a ‘Digital Islamic Parenting’ community has been formed as a platform for ongoing learning. These findings indicate that integrating Islamic communication into an educational-participatory approach can strengthen the resilience of Muslim families in facing the challenges of the digital age.